Current pandemic COVID-19 vaccine strategies and development: a comprehensive review - Hayat Ullah (VacciMonitor, 2023)
The coronavirus disease-19 pandemic with the characteristics of asymptomatic condition, long incubation period and poor treatment has influenced the entire globe. Coronaviruses are important emergent pathogens, specifically, the recently emerged sever acute respiratory syndrome coronavirus 2, the causative virus of the current COVID-19 pandemic. To mitigate the virus and curtail the infection risk, vaccines are the most hopeful solution. The protein structure and genome sequence of SARS-CoV-2 were processed and provided in record time; providing feasibility to the development of COVID-19 vaccines. In an unprecedented scientific and technological effort, vaccines against SARS-CoV-2 have been developed in less than one year. This review addresses the approaches adopted for SARS-CoV-2 vaccine development and the effectiveness of the currently approved vaccines.